(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper provides an overarching analysis of the key elements of the future ports and maritime logistics, particularly from sustainability perspective. This is followed by a discussion of current, emerging and potential strategies, covering main trends and long term challenges to realize more sustainable practices, the different interest groups involved and also the importance and changing nature of ports and maritime logistics regulation. Research inductive and deductive methods are used in order to express the main scientific aspects of sustainability of future ports and maritime logistics.